Colloidal Au/iron oxide nanocrystal heterostructures: magnetic, plasmonic and magnetic hyperthermia properties. Issue 45 (6th November 2018) - Vita, Francesco; Innocenti, Claudia; Secchi, Andrea; Albertini, Franca; Grillo, Vincenzo; Fiore, Angela; Cozzoli, P. Davide; de Julián Fernández, César
Abstract : Interface and morphology determine the magnetic, plasmonic and magnetic hyperthermia properties of Au/iron oxide nanocrystal heterostructures. Abstract : Colloidal magneto-plasmonic nanostructures are multifunctional materials with huge potential for applications in magnetism, optoelectronics, biomedicine and catalysis. Currently it is considered that their optical and magnetic properties are a combination of the modified properties associated with the material constituents. Herein we have investigated the morphological, magnetic and plasmonic properties of Au@magnetite core@shell heterostructured nanocrystals (HNCs) with eccentric topology. We shed light on their behavior as heat mediators for magnetic fluid hyperthermia, a promising approach to cancer therapy. A red-shift and damping of the plasmon resonance was observed, which correlated with the optical contribution and the dielectric screening of the asymmetrically distributed iron oxide shell. The magnetic properties of the Au@magnetite HNCs were investigated by comparison with those of the corresponding carved magnetite nanocrystals (NCs), obtained by selective etching of the Au domain with iodine. The iron oxide NCs featured higher magnetization and coercive field than their parent HNCs, which showed a superparamagnetic behavior instead. In addition, the carved NCs exhibited better hyperthermia performances than the HNCs, being the Specific Absorption Rate (SAR) of heat one order of magnitude higher. On the basis of the peculiar magnetic properties of the HNCs, we hypothesized that a minority wüstite phase was stabilized at the Au/iron-oxide interface, which could be eliminated upon oxidation to magnetite during the Au etching process. Our study opens a new scenario in the understanding of the physico-chemical behavior of this class of magneto-plasmonic heterostructures, whereby the asymmetric spatial distribution of the component materials, their complex multiphase composition and hetero-interface structure determine their ultimate plasmonic, magnetic and hyperthermia properties.